A 21st century plague of biblical proportions. (9th September 2018) - Biggin, Andrew
Abstract: Modern medicine has eradicated smallpox, contained polio and is making significant advances in personalised/genetic medicine.1 2 However, we are facing a pandemic of apocalyptic proportions, and there is currently no vaccine or United Nations Charter to help address this issue. Following its insidious spread in the 1980s, the full impact of this phenomenon on civilisation has not been fully appreciated. It has slipped under the radar of the International Classification of Diseases (ICD‐10) and Diagnostic and Statistical Manual of Mental Disorders (DSM‐5) classification systems. We all know someone who is affected by this condition, and society is struggling to cope with the acute and chronic morbidity that has ensued. I am, of course, referring to the problem of the workplace email. This article examines the problems associated with workplace email and aims to offer some strategies to help contain it.